2022
DOI: 10.3389/fped.2021.780258
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Fatal Acute Liver Failure With Giant Cell Transformation in a Pediatric Patient Associated With MIS-C

Abstract: Background: We describe the first pediatric case of a 10-month-old boy with MIS-C who developed fulminant acute liver failure with associated giant cell transformation and a fatal outcome, after ruling out other infectious, metabolic, genetic, and autoimmune causes of liver failure following the usual algorithms for approaching the etiology. Although the patient received the main treatment strategies for liver failure, he had a fatal outcome. A clinical autopsy was considered as part of the diagnostic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Unfortunately, there are very few autopsy studies on MIS-C reported to date, to which we can compare our finding. Four cases are from South America and a fifth from Spain [12] , [13] , [14] , [15] . Ages ranged from 8 to 12 years except one case at 10 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, there are very few autopsy studies on MIS-C reported to date, to which we can compare our finding. Four cases are from South America and a fifth from Spain [12] , [13] , [14] , [15] . Ages ranged from 8 to 12 years except one case at 10 months.…”
Section: Discussionmentioning
confidence: 99%
“…Affected organs included heart, lung, colon and brain, and involved cell types including cardiac myocytes, endothelial cells, macrophages, neutrophils, renal tubular epithelial cells, colonic glands, and fibroblasts. The fifth case, the one of hepatic failure [12] is unusual for MIS-C in many ways. The patient was only 10 months, which is younger than the median age of 8 years for MIS-C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a 14-year-old boy developed MIS-C after SARS-COV-2 infection which was followed by hepatic steatosis, and the researchers also found elevated levels of ALT, AST and indices of cholestasis[ 54 ]. Another 10-month-old boy developed fulminant acute liver failure due to MIS-C[ 55 ]. The pathophysiology of MIS-C-mediated liver injury may also be related to the IIR as described previously.…”
Section: Indirect Pathophysiological Mechanismsmentioning
confidence: 99%